Laminate and packaging material composed of the laminate
Patent Information
- Application Number
- JP2024069346
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-03-26
- Filing Date
- 2024-04-22
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2039-03-22
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate and a packaging material comprising said laminate. [Background technology]
[0002] Polyethylene films are used in various packaging materials because they have moderate flexibility, excellent transparency, moisture resistance, chemical resistance, etc., and are inexpensive. In particular, the melting point of polyethylene is generally about 100 to 140°C, although this varies slightly depending on the type, so in the packaging material field, it is generally used as a heat-sealable film.
[0003] On the other hand, compared with other thermoplastic resin films, polyethylene films have poor rigidity, and therefore have low printability, and it has not been possible to form clear images on their surfaces. In addition, polyethylene films do not have high strength, and have not been able to meet the durability required for the exterior of packaging materials. For this reason, a resin film having excellent rigidity and strength, such as a polyester film or a nylon film, is laminated with a polyethylene film to form a laminate, and the ends of the laminate are heat-sealed so that the polyethylene film side of the laminate is on the inside, thereby producing a packaging material (for example, JP 2005-104525 A).
[0004] In recent years, along with the growing demand for the creation of a recycling-oriented society, attempts have been made to recycle and reuse packaging materials. However, when different types of resin films are laminated together as described above, it is difficult to separate the resin films from each other, making them unsuitable for recycling, and there has been a demand for using packaging materials that impose less of a burden on the environment.
[0005] Depending on the type of contents, the packaging material may be required to have high gas barrier properties. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2005-104525 A Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been made to solve the above problems, and an object of the present invention is to provide a laminate having high recyclability, printability, strength and gas barrier properties. [Means for solving the problem]
[0008] In a first aspect, the laminate of the present invention comprises at least a substrate and a heat-sealable polyethylene layer, the substrate and the heat-sealable layer being made of the same material, the substrate being subjected to a stretching treatment, the stretched polyethylene film substrate having a vapor deposition film on at least one surface thereof, and the same material being polyethylene.
[0009] In one embodiment, the substrate comprises a deposited film that includes aluminum oxide.
[0010] In one embodiment, the laminate further comprises an intermediate layer between the substrate and the heat seal layer, the intermediate layer being made of polyethylene and having a vapor deposition film on at least one surface thereof.
[0011] In one embodiment, the intermediate layer comprising the vapor-deposited film consists of a stretched polyethylene film and a vapor-deposited film.
[0012] In one embodiment, the substrate comprises at least one of high density polyethylene (HDPE) and medium density polyethylene (MDPE).
[0013] In one embodiment, the stretching ratio in the machine direction (MD) of the substrate is 2 times or more and 10 times or less.
[0014] In one embodiment, the thickness of the substrate is 9 μm or more and 50 μm or less.
[0015] In one embodiment, the substrate comprises a high density polyethylene layer, a medium density polyethylene layer, and a high density polyethylene layer.
[0016] In one embodiment, the substrate is a five-layer co-extruded film consisting of a high density polyethylene layer, a medium density polyethylene layer, a low density polyethylene layer, a linear low density polyethylene layer or a very low density polyethylene layer, a medium density polyethylene layer, and a high density polyethylene layer.
[0017] In one embodiment, the substrate is a seven-layer co-extruded film consisting of a high-density polyethylene layer, a blend resin layer of high-density polyethylene and medium-density polyethylene, a medium-density polyethylene layer, a low-density polyethylene layer, a linear low-density polyethylene layer or a very low-density polyethylene layer, a medium-density polyethylene layer, a blend resin layer of high-density polyethylene and medium-density polyethylene, and a high-density polyethylene layer.
[0018] In one embodiment, the heat seal layer comprises at least one of low density polyethylene (LDPE) and linear low density polyethylene (LLDPE).
[0019] In a second aspect, the laminate of the present invention comprises a substrate, a polyethylene intermediate layer having a vapor-deposited film on at least one surface thereof, and a heat-sealable polyethylene layer heat-sealing layer, the substrate, intermediate layer and heat-sealing layer being made of the same material, the intermediate layer having a vapor-deposited film on at least one surface thereof, the substrate being subjected to a stretching treatment, and the same material being polyethylene.
[0020] In one embodiment, the intermediate layer comprising a vapor-deposited film comprises a vapor-deposited film that includes aluminum.
[0021] In one embodiment, the intermediate layer comprising the vapor-deposited film consists of a stretched polyethylene film and a vapor-deposited film.
[0022] In one embodiment, the substrate comprises at least one of high density polyethylene (HDPE) and medium density polyethylene (MDPE).
[0023] In one embodiment, the stretching ratio in the machine direction (MD) of the substrate is 2 times or more and 10 times or less.
[0024] In one embodiment, the thickness of the substrate is 9 μm or more and 50 μm or less.
[0025] In one embodiment, the substrate comprises a high density polyethylene layer, a medium density polyethylene layer, and a high density polyethylene layer.
[0026] In one embodiment, the substrate is a five-layer co-extruded film consisting of a high density polyethylene layer, a medium density polyethylene layer, a low density polyethylene layer, a linear low density polyethylene layer or a very low density polyethylene layer, a medium density polyethylene layer, and a high density polyethylene layer.
[0027] In one embodiment, the substrate is a seven-layer co-extruded film consisting of a high-density polyethylene layer, a blend resin layer of high-density polyethylene and medium-density polyethylene, a medium-density polyethylene layer, a low-density polyethylene layer, a linear low-density polyethylene layer or a very low-density polyethylene layer, a medium-density polyethylene layer, a blend resin layer of high-density polyethylene and medium-density polyethylene, and a high-density polyethylene layer.
[0028] In one embodiment, the heat seal layer comprises at least one of low density polyethylene (LDPE) and linear low density polyethylene (LLDPE).
[0029] The packaging material of the present invention is characterized in that it is composed of the above-mentioned laminate. Effect of the Invention
[0030] According to the present invention, it is possible to provide a laminate having high recyclability, printability, strength and gas barrier properties. [Brief description of the drawings]
[0031] [Figure 1] 1 is a cross-sectional schematic diagram showing one embodiment of a laminate according to a first aspect. [Diagram 2] 1 is a cross-sectional schematic diagram showing one embodiment of a laminate according to a first aspect. [Diagram 3] FIG. 2 is a cross-sectional schematic diagram showing one embodiment of a laminate according to a second aspect. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] <Laminate of the First Aspect> The laminate according to the present invention will now be described with reference to the drawings. As shown in FIG. 1, the laminate 10 of the first embodiment comprises at least a substrate 20 and a heat seal layer 30, and a vapor-deposited film 40 on at least one surface of the substrate 20. Furthermore, the laminate 10 of the first embodiment may have an intermediate layer 50 between the substrate 20 and the heat seal layer 30, the intermediate layer having a vapor-deposited film 40 on at least one surface thereof, as shown in FIG. Each layer of the laminate will now be described.
[0033] <Base material> The substrate is one that has been subjected to a stretching treatment, and may be one that has been uniaxially stretched or one that has been biaxially stretched. From the viewpoint of strength, however, one that has been biaxially stretched is preferred.
[0034] The stretching ratio in the longitudinal direction (MD) of the substrate is preferably 2 times or more and 10 times or less, and more preferably 3 times or more and 7 times or less. This can further improve the printability and strength of the laminate. In addition, this can improve the transparency of the substrate. The stretching ratio in the transverse direction (TD) is preferably 2 to 10 times, and more preferably 3 to 7 times, which can improve the printability and strength of the laminate and can also improve its transparency.
[0035] The substrate is made of polyethylene, and examples of polyethylene include high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), and linear low density polyethylene (LLDPE). The substrate may contain two or more of these. Among these, high density polyethylene (HDPE) and medium density polyethylene (MDPE) are preferred from the viewpoints of printability, strength and heat resistance of the laminate, and medium density polyethylene is more preferred from the viewpoint of suitability for stretching. In the present invention, the high density polyethylene has a density of 0.945 g / cm 3 The above is classified as medium density polyethylene, which has a density of 0.925 to 0.944 g / cm 3 Low density polyethylene has a density of 0.900g / cm 3 More than 0.925g / cm 3 Ultra-low density polyethylene has a density of less than 0.900 g / cm 3 It refers to something less than.
[0036] The polyethylenes having different densities and branches as described above can be obtained by appropriately selecting a polymerization method. For example, it is preferable to use a multi-site catalyst such as a Ziegler-Natta catalyst or a single-site catalyst such as a metallocene catalyst as a polymerization catalyst and carry out the polymerization in one stage or in two or more stages by any of gas phase polymerization, slurry polymerization, solution polymerization, and high pressure ion polymerization.
[0037] The single-site catalyst is a catalyst capable of forming a uniform active species, and is usually prepared by contacting a metallocene transition metal compound or a nonmetallocene transition metal compound with an activating cocatalyst. Compared with a multi-site catalyst, a single-site catalyst is preferred because it has a uniform active site structure and can polymerize a polymer with a high molecular weight and a highly uniform structure. As the single-site catalyst, it is particularly preferred to use a metallocene catalyst. The metallocene catalyst is a catalyst containing each catalyst component of a transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton, a cocatalyst, and if necessary, an organometallic compound and a carrier.
[0038] In the above-mentioned transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton, the cyclopentadienyl skeleton is a cyclopentadienyl group, a substituted cyclopentadienyl group, etc. The substituted cyclopentadienyl group has at least one substituent selected from a hydrocarbon group having 1 to 30 carbon atoms, a silyl group, a silyl-substituted alkyl group, a silyl-substituted aryl group, a cyano group, a cyanoalkyl group, a cyanoaryl group, a halogen group, a haloalkyl group, a halosilyl group, etc. The substituted cyclopentadienyl group may have two or more substituents, and the substituents may be bonded to each other to form a ring, such as an indenyl ring, a fluorenyl ring, an azulenyl ring, or a hydrogenated product thereof. The rings formed by bonding the substituents to each other may further have substituents.
[0039] In the transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton, the transition metal may be zirconium, titanium, hafnium, etc., and zirconium and hafnium are particularly preferred. The transition metal compound usually has two ligands having a cyclopentadienyl skeleton, and each ligand having a cyclopentadienyl skeleton is preferably bonded to each other by a bridging group. The bridging group may be an alkylene group having 1 to 4 carbon atoms, a silylene group, a substituted silylene group such as a dialkylsilylene group or a diarylsilylene group, or a substituted germylene group such as a dialkylgermylene group or a diarylgermylene group. The substituted silylene group is preferred. The above-mentioned transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton may be used as a catalyst component, either alone or in a mixture of two or more kinds.
[0040] The co-catalyst refers to a catalyst that can effectively use the above-mentioned transition metal compound of Group IV of the periodic table as a polymerization catalyst or balance the ionic charge in a catalytically activated state. Examples of the co-catalyst include benzene-soluble aluminoxanes of organoaluminum oxy compounds and benzene-insoluble organoaluminum oxy compounds, ion-exchangeable layered silicates, boron compounds, ionic compounds consisting of cations containing or not containing active hydrogen groups and non-coordinating anions, lanthanoid salts such as lanthanum oxide, tin oxide, and phenoxy compounds containing fluoro groups.
[0041] The transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton may be used by being supported on an inorganic or organic carrier. The carrier is preferably an inorganic or organic porous oxide, and specifically includes ion-exchangeable layered silicates such as montmorillonite, SiO2, Al2O3, MgO, ZrO2, TiO2, B2O3, CaO, ZnO, BaO, ThO2, etc., or mixtures thereof. Furthermore, examples of organometallic compounds that may be used as needed include organoaluminum compounds, organomagnesium compounds, and organozinc compounds. Of these, organoaluminum compounds are preferably used.
[0042] In addition, copolymers of ethylene and other monomers can also be used within the scope of the present invention. Examples of ethylene copolymers include copolymers of ethylene and α-olefins having 3 to 20 carbon atoms, and examples of α-olefins having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, 4-methyl-1-pentene, and 6-methyl-1-heptene. In addition, copolymers with vinyl acetate, acrylic esters, etc. can also be used within the scope of the present invention.
[0043] In addition, in the present invention, biomass-derived ethylene may be used as a raw material for obtaining the above-mentioned high-density polyethylene, instead of ethylene obtained from fossil fuels. Since such biomass-derived polyethylene is a carbon-neutral material, it can be used as a packaging material with even less environmental impact. Such biomass-derived polyethylene can be produced, for example, by a method such as that described in JP 2013-177531 A. In addition, commercially available biomass-derived polyethylene (for example, Green PE commercially available from Braskem) may be used.
[0044] The content of polyethylene in the substrate is preferably 50% by mass or more, and more preferably 70% by mass or more.
[0045] The substrate may contain additives within the range that does not impair the characteristics of the present invention. For example, crosslinking agents, antioxidants, ultraviolet absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, modifying resins, etc. may be mentioned.
[0046] In one embodiment, the substrate has a multi-layer structure. In one embodiment, the substrate may have a structure including a layer made of high density polyethylene (hereinafter referred to as high density polyethylene layer) and a layer made of medium density polyethylene (hereinafter referred to as medium density polyethylene layer). By providing a high density polyethylene layer on the outer side of the substrate, the strength and heat resistance of the laminate of the present invention can be further improved, and by providing a medium density polyethylene layer, the stretchability of the substrate can be further improved.
[0047] For example, it has a structure consisting of a co-extruded film of a high density polyethylene layer and a medium density polyethylene layer from the outside. By adopting such a constitution, the stretchability of the substrate can be improved, and the strength and heat resistance of the laminate of the present invention can be improved. In this case, the thickness of the high density polyethylene layer is preferably thinner than the thickness of the medium density polyethylene layer. The ratio of the thickness of the high density polyethylene layer to the thickness of the medium density polyethylene layer is preferably 1 / 10 or more and 1 / 1 or less, and more preferably 1 / 5 or more and 1 / 2 or less. By setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer to be 1 / 10 or more, the strength and heat resistance of the laminate of the present invention can be further improved. Also, by setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer to be 1 / 1 or less, the stretchability of the substrate can be further improved.
[0048] Also, for example, it may be configured to have a three-layer co-extruded film consisting of a high density polyethylene layer, a medium density polyethylene layer and a high density polyethylene layer from the outside. By adopting such a constitution, the stretchability of the substrate can be further improved, the strength and heat resistance of the laminate of the present invention can be further improved, and the occurrence of curling in the substrate can be prevented. In this case, the thickness of the high density polyethylene layer is preferably thinner than the thickness of the medium density polyethylene layer. The ratio of the thickness of the high density polyethylene layer to the thickness of the medium density polyethylene layer is preferably 1 / 10 or more and 1 / 1 or less, and more preferably 1 / 5 or more and 1 / 2 or less. By setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer to be 1 / 10 or more, the strength and heat resistance of the laminate of the present invention can be further improved. Also, by setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer to be 1 / 1 or less, the stretchability of the substrate can be further improved.
[0049] Also, for example, it may be configured as a five-layer co-extruded film consisting of, from the outside, a high-density polyethylene layer, a medium-density polyethylene layer, a low-density polyethylene layer, a linear low-density polyethylene layer or an ultra-low-density polyethylene layer (in this paragraph, for simplicity, they are collectively referred to as a low-density polyethylene layer), a medium-density polyethylene layer and a high-density polyethylene layer. By adopting such a constitution, it is possible to improve the stretchability of the substrate, to improve the strength and heat resistance of the laminate of the present invention, and to prevent the substrate from curling. Furthermore, the production efficiency of the substrate can be improved as described below. In this case, the thickness of the high density polyethylene layer is preferably thinner than the thickness of the medium density polyethylene layer. The ratio of the thickness of the high density polyethylene layer to the thickness of the medium density polyethylene layer is preferably 1 / 10 or more and 1 / 1 or less, and more preferably 1 / 5 or more and 1 / 2 or less. By setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer to be 1 / 10 or more, the strength and heat resistance of the laminate of the present invention can be improved. Also, by setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer to be 1 / 1 or less, the stretchability of the substrate can be improved. In addition, the thickness of the high density polyethylene layer is preferably the same as or greater than the thickness of the low density polyethylene layer. The ratio of the thickness of the high density polyethylene layer to the thickness of the low density polyethylene layer is preferably 1 / 0.25 or more and 1 / 2 or less, and more preferably 1 / 0.5 or more and 1 / 1 or less. By setting the ratio of the thickness of the high density polyethylene layer to the thickness of the low density polyethylene layer to 1 / 0.25 or more, the heat resistance can be improved, and by setting the ratio of the thickness of the high density polyethylene layer to the thickness of the low density polyethylene layer to 1 / 1 or less, the adhesion between the medium density polyethylene layers can be improved. The thickness of each high-density polyethylene layer is preferably 1 μm or more and 20 μm or less, and more preferably 2 μm or more and 10 μm or less. By making the thickness of the high-density polyethylene layer 1 μm or more, the strength and heat resistance of the laminate of the present invention can be further improved. In addition, by making the thickness of the high-density polyethylene layer 20 μm or less, the processability of the laminate of the present invention can be further improved. The thickness of the medium-density polyethylene layer is preferably 1 μm or more and 30 μm or less, and more preferably 5 μm or more and 20 μm or less. By making the thickness of the medium-density polyethylene layer 1 μm or more, the stretchability of the substrate can be further improved. In addition, by making the thickness of the medium-density polyethylene layer 30 μm or less, the processability of the laminate of the present invention can be further improved. The thickness of the low-density polyethylene layer is preferably 1 μm or more and 10 μm or less, and more preferably 2 μm or more and 5 μm or less. By making the thickness of the low-density polyethylene layer 1 μm or more, the adhesion between the high-density polyethylene layer and the medium-density polyethylene layer can be further improved, and by making the thickness of the low-density polyethylene layer 5 μm or less, the processability of the laminate of the present invention can be further improved. In one embodiment, a substrate having such a configuration can be produced by, for example, an inflation method. Specifically, the film can be produced by co-extruding, from the outside, a high-density polyethylene layer, a medium-density polyethylene layer, and a low-density polyethylene layer, a linear low-density polyethylene layer, or an ultra-low-density polyethylene layer into a tubular shape, and then pressing the opposing low-density polyethylene layers, linear low-density polyethylene layers, or ultra-low-density polyethylene layers together using a rubber roll or the like. By using such a method, the number of defective products during manufacturing can be significantly reduced, and ultimately, production efficiency can be improved. In addition, the stretching can also be carried out in the inflation film forming machine, which can further improve the production efficiency.
[0050] In one embodiment, the seven-layer co-extruded film may be configured to include, from the outside, a high-density polyethylene layer, a blend resin layer of high-density polyethylene and medium-density polyethylene, a medium-density polyethylene layer, a low-density polyethylene layer, a linear low-density polyethylene layer or an ultra-low-density polyethylene layer (in this paragraph, for simplicity, these are collectively referred to as low-density polyethylene layers), a medium-density polyethylene layer, a blend resin layer of high-density polyethylene and medium-density polyethylene, and a high-density polyethylene layer. By adopting such a structure, it is possible to improve the adhesion between the high density polyethylene layer and the medium density polyethylene layer, and also to improve the processability of the laminate of the present invention. The thickness of each high-density polyethylene layer is preferably 1 μm or more and 20 μm or less, and more preferably 2 μm or more and 10 μm or less. By making the thickness of the high-density polyethylene layer 1 μm or more, the strength and heat resistance of the laminate of the present invention can be further improved. In addition, by making the thickness of the high-density polyethylene layer 20 μm or less, the processability of the laminate of the present invention can be further improved. The thickness of each blend resin layer of high density polyethylene and medium density polyethylene is preferably 1 μm or more and 20 μm or less, more preferably 2 μm or more and 10 μm or less. This can improve the adhesion between the high density polyethylene layer and the medium density polyethylene layer. In addition, the processability of the laminate of the present invention can be improved. The blending ratio of the high density polyethylene to the medium density polyethylene in the blend resin layer is preferably 1:9 to 9:1, more preferably 3:7 to 7:3, on a mass basis. This can improve the adhesion between the high density polyethylene layer and the medium density polyethylene layer, and can also improve the processability of the laminate of the present invention. The thickness of the medium-density polyethylene layer is preferably 1 μm or more and 30 μm or less, and more preferably 5 μm or more and 20 μm or less. By making the thickness of the medium-density polyethylene layer 1 μm or more, the stretchability of the substrate can be further improved. In addition, by making the thickness of the medium-density polyethylene layer 30 μm or less, the processability of the laminate of the present invention can be further improved. The thickness of the low-density polyethylene layer is preferably 1 μm or more and 10 μm or less, and more preferably 2 μm or more and 5 μm or less. By making the thickness of the low-density polyethylene layer 1 μm or more, the adhesion between the high-density polyethylene layer and the medium-density polyethylene layer can be further improved, and by making the thickness of the low-density polyethylene layer 5 μm or less, the processability of the laminate of the present invention can be further improved. In one embodiment, a substrate having such a configuration can be produced by the inflation method described above. By using such a method, the number of defective products during manufacturing can be significantly reduced, and ultimately, production efficiency can be improved. In addition, the stretching can also be carried out in the inflation film forming machine, which can further improve the production efficiency.
[0051] The thickness of the substrate is preferably 9 μm or more and 50 μm or less, and more preferably 12 μm or more and 30 μm or less. By setting the thickness of the substrate within the above numerical range, the printability, strength, and heat resistance of the laminate can be further improved.
[0052] In the first embodiment, the substrate has a vapor-deposited film on at least one surface thereof. From the viewpoint of adhesion to the heat seal layer, it is preferable that the vapor-deposited film is provided on the side of the substrate opposite to the side on which the heat seal layer is provided.
[0053] Examples of materials constituting the vapor-deposited film include metals such as aluminum, aluminum oxide, and inorganic oxides such as silicon oxide, magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, and barium oxide. Among the above, it is preferable to form a vapor deposition film from aluminum oxide, since it has high transparency, does not reduce the visibility of an image formed on the substrate, and has excellent gas barrier properties.
[0054] The thickness of the vapor-deposited film is preferably 0.002 μm or more and 0.4 μm or less, and more preferably 0.005 μm or more and 0.1 μm or less. By setting the thickness of the vapor-deposited film within the above numerical range, it is possible to prevent the occurrence of cracks in the vapor-deposited film while maintaining the gas barrier properties.
[0055] The substrate may have an image such as a letter, a pattern, a symbol, etc. formed on its surface. In order to prevent deterioration of the image over time, it is preferable to form the image on the side of the substrate where the heat seal layer is laminated. The method for forming the image is not particularly limited, and examples of the method include conventionally known printing methods such as gravure printing, offset printing, flexographic printing, etc. Among these, flexographic printing is preferred from the viewpoint of environmental load.
[0056] The substrate can be obtained by melting a resin material containing polyethylene, forming it into a film by a melt extrusion molding method such as inflation molding or T-die molding, and then stretching it. Since the stretching process can be performed more easily, it is preferable to prepare it by the inflation molding method. A substrate having a multilayer structure can be prepared by melt co-extruding multiple resin materials.
[0057] The melt flow rate (MFR) of the resin material is preferably 0.5 g / 10 min or more and 20 g / 10 min or less, more preferably 0.8 g / 10 min or more and 5 g / 10 min or less. By setting the MFR of the resin material within the above numerical range, the stretching process can be performed more easily.
[0058] As a method for forming a vapor-deposited film, a conventionally known method can be used, for example, a physical vapor deposition method (PVD method) such as a vacuum deposition method, a sputtering method, or an ion plating method, or a chemical vapor deposition method (CVD method) such as a plasma chemical vapor deposition method, a thermal chemical vapor deposition method, or a photochemical vapor deposition method.
[0059] Also, for example, a composite film consisting of two or more layers of vapor-deposited films of different inorganic oxides can be formed and used by combining both physical vapor deposition and chemical vapor deposition. The degree of vacuum in the vapor deposition chamber is preferably about 10-2 to 10-8 mbar, particularly about 10-3 to 10-7 mbar, before oxygen is introduced, and is preferably about 10-1 to 10-6 mbar, particularly about 10-2 to 10-5 mbar, after oxygen is introduced. The amount of oxygen introduced varies depending on the size of the vapor deposition machine. For the oxygen to be introduced, an inert gas such as argon gas, helium gas, or nitrogen gas may be used as a carrier gas within a range that does not cause any problems. The film transport speed is preferably about 10 to 800 m / min, particularly about 50 to 600 m / min.
[0060] In one embodiment, the substrate may include a barrier coat layer, which may improve the oxygen and water vapor barrier properties. When the substrate has a vapor-deposited film, the barrier coat layer may be provided on or under the vapor-deposited film.
[0061] In one embodiment, the barrier coat layer contains a gas barrier resin such as an ethylene-vinyl alcohol copolymer (EVOH), polyvinyl alcohol, polyacrylonitrile, polyamide such as nylon 6, nylon 6,6, and polymetaxylylene adipamide (MXD6), polyester, polyurethane, and (meth)acrylic resin. Among these, polyvinyl alcohol is preferred from the viewpoint of oxygen barrier property and water vapor barrier property. Furthermore, when the substrate has a vapor-deposited film made of an inorganic oxide, the occurrence of cracks in the vapor-deposited film can be effectively prevented by including polyvinyl alcohol in the barrier coat layer.
[0062] The content of the gas barrier resin in the barrier coat layer is preferably 50% by mass or more and 95% by mass or less, and more preferably 75% by mass or more and 90% by mass or less. By making the content of the gas barrier resin in the barrier coat layer 50% by mass or more, the oxygen barrier property and water vapor barrier property can be further improved.
[0063] The barrier coat layer may contain additives as long as they do not impair the characteristics of the present invention.
[0064] The thickness of the barrier coat layer is preferably 0.01 μm or more and 10 μm or less, and more preferably 0.1 μm or more and 5 μm or less. By making the thickness of the barrier coat layer 0.01 μm or more, the oxygen barrier property and water vapor barrier property can be further improved, and by making the thickness of the barrier coat layer 10 μm or less, recyclability can be maintained.
[0065] The barrier coat layer can be formed by dissolving or dispersing the above-mentioned material in water or a suitable solvent, applying the solution, and drying the solution. Alternatively, the barrier coat layer can be formed by applying a commercially available barrier coat agent and drying the solution.
[0066] In another embodiment, the barrier coat layer is a gas barrier coating film containing at least one resin composition such as a hydrolysate of a metal alkoxide or a hydrolyzed condensate of a metal alkoxide obtained by polycondensing a mixture of a metal alkoxide and a water-soluble polymer by a sol-gel method in the presence of a sol-gel catalyst, water, an organic solvent, etc. When the substrate has a vapor-deposited film made of an inorganic oxide, by providing the barrier coat layer of this type adjacent to the vapor-deposited film, it is possible to effectively prevent the occurrence of cracks in the vapor-deposited film.
[0067] In one embodiment, the metal alkoxide is represented by the following general formula: R 1 n M(OR 2 ) m (In the formula, R 1 , R 2 each represents an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M.
[0068] As the metal atom M, for example, silicon, zirconium, titanium, aluminum, etc. can be used. Also, R 1 and R 2 Examples of the organic group represented by the formula (I) include alkyl groups such as a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, and an i-butyl group.
[0069] Examples of metal alkoxides that satisfy the above general formula include tetramethoxysilane (Si(OCH3)4), tetraethoxysilane (mass %) Si(OC2H5)4), tetrapropoxysilane (Si(OC3H7)4), and tetrabutoxysilane (Si(OC4H9)4).
[0070] It is also preferable to use a silane coupling agent together with the metal alkoxide. As the silane coupling agent, known organic reactive group-containing organoalkoxysilanes can be used, and in particular, organoalkoxysilanes having epoxy groups are preferred. As organoalkoxysilanes having epoxy groups, for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can be mentioned.
[0071] Two or more of the above silane coupling agents may be used, and the silane coupling agent is preferably used in an amount within the range of about 1 to 20 parts by mass per 100 parts by mass of the total amount of the alkoxide.
[0072] As the water-soluble polymer, polyvinyl alcohol and an ethylene-vinyl alcohol copolymer are preferred, and from the viewpoints of oxygen barrier properties, water vapor barrier properties, water resistance and weather resistance, it is preferred to use these in combination.
[0073] The content of the water-soluble polymer in the gas barrier coating film is preferably 5 parts by mass or more and 500 parts by mass or less per 100 parts by mass of the metal alkoxide. By making the content of the water-soluble polymer in the gas barrier coating film 5 parts by mass or more per 100 parts by mass of the metal alkoxide, the oxygen barrier property and water vapor barrier property of the substrate can be further improved. Also, by making the content of the water-soluble polymer in the gas barrier coating film 500 parts by mass or less per 100 parts by mass of the metal alkoxide, the film formability of the gas barrier coating film can be improved.
[0074] The thickness of the gas barrier coating film is preferably from 0.01 μm to 100 μm, and more preferably from 0.1 μm to 50 μm, which can improve the oxygen barrier property and water vapor barrier property while maintaining recyclability. By making the thickness of the gas barrier coating film 0.01 μm or more, the oxygen barrier property and water vapor barrier property of the substrate can be improved. In addition, when the gas barrier coating film is provided adjacent to a vapor deposition film made of an inorganic oxide, the occurrence of cracks in the vapor deposition film can be prevented.
[0075] The gas barrier coating film can be formed by applying a composition containing the above-mentioned materials by a conventionally known means such as roll coating using a gravure roll coater or the like, spray coating, spin coating, dipping, brushing, bar coding, or an applicator, and then polycondensing the composition by a sol-gel method. As the sol-gel catalyst, an acid or an amine compound is preferable. As the amine compound, a tertiary amine that is substantially insoluble in water and soluble in an organic solvent is preferable, and examples thereof include N,N-dimethylbenzylamine, tripropylamine, tributylamine, and tripentylamine. Among these, N,N-dimethylbenzylamine is preferable. The sol-gel catalyst is preferably used in the range of 0.01 to 1.0 part by mass, and more preferably 0.03 to 0.3 part by mass, per 100 parts by mass of the metal alkoxide. By using a sol-gel catalyst in an amount of 0.01 part by mass or more per 100 parts by mass of the metal alkoxide, the catalytic effect can be improved, and by using a sol-gel catalyst in an amount of 1.0 part by mass or less per 100 parts by mass of the metal alkoxide, the thickness of the gas barrier coating film formed can be made uniform.
[0076] The composition may further contain an acid, which is used as a catalyst in the sol-gel process, mainly for the hydrolysis of alkoxides, silane coupling agents, and the like. The acid may be a mineral acid such as sulfuric acid, hydrochloric acid, or nitric acid, or an organic acid such as acetic acid, tartaric acid, etc. The amount of the acid used is preferably 0.001 mol or more and 0.05 mol or less based on the total molar amount of the alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent. The amount of acid used is 0.001 moles or more relative to the total molar amount of the alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent, thereby improving the catalytic effect. Also, the amount of acid used is 0.05 moles or less relative to the total molar amount of the alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent, thereby making the thickness of the gas barrier coating film formed uniform.
[0077] The composition preferably contains water in an amount of 0.1 to 100 moles, more preferably 0.8 to 2 moles, per mole of the total molar amount of the alkoxides. By controlling the water content to 0.1 moles or more per mole of the total amount of alkoxides, the oxygen barrier property and water vapor barrier property can be improved, and by controlling the water content to 100 moles or more per mole of the total amount of alkoxides, the hydrolysis reaction can be carried out quickly.
[0078] The composition may also contain an organic solvent, such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, or n-butanol.
[0079] Hereinafter, one embodiment of the method for forming a gas barrier coating film will be described. First, a composition is prepared by mixing a metal alkoxide, a water-soluble polymer, a sol-gel catalyst, water, an organic solvent, and optionally a silane coupling agent, etc. In the composition, a polycondensation reaction gradually proceeds. Next, the composition is applied and dried by the above-mentioned conventionally known method. This drying process further advances the polycondensation reaction between the alkoxide and the water-soluble polymer (and the silane coupling agent, if the composition contains a silane coupling agent) to form a composite polymer layer. Finally, the composition is heated at a temperature of 20 to 250° C., preferably 50 to 220° C., for 1 second to 10 minutes to form a gas barrier coating film.
[0080] The barrier coat layer may have an image formed on its surface. The method for forming the image is as described above.
[0081] <Heat seal layer> The heat seal layer is made of the same material as the base material, i.e., polyethylene, which can improve the recyclability of the laminate. The heat seal layer contains at least one of high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and a copolymer of ethylene and other monomers. Among these, low density polyethylene (LDPE) and linear low density polyethylene (LLDPE) are preferred from the viewpoint of heat sealability. From the viewpoint of environmental load, these polyethylenes are preferably derived from biomass.
[0082] The content of polyethylene in the heat seal layer is preferably 50% by mass or more, and more preferably 70% by mass or more.
[0083] The heat seal layer may contain additives within the range that does not impair the characteristics of the present invention. For example, crosslinking agents, antioxidants, ultraviolet absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, modifying resins, etc. may be included.
[0084] The thickness of the heat seal layer is preferably 20 μm or more and 200 μm or less, and more preferably 30 μm or more and 150 μm or less. By setting the thickness of the heat seal layer within the above numerical range, the heat sealability can be improved.
[0085] The heat seal layer can be formed by producing a polyethylene film by forming a resin material containing polyethylene into a film by a melt extrusion molding method such as inflation molding or T-die molding, and laminating this onto a polyethylene layer having a substrate or a vapor deposition film via an adhesive layer. The adhesive layer includes an adhesive, the adhesive comprising: The adhesive may be a one-component curing type, a two-component curing type, or a non-curing type. The adhesive may be a solvent-free adhesive or a solvent-based adhesive, but from the viewpoint of environmental load, a solvent-free adhesive is preferably used. Examples of solvent-free adhesives include polyether adhesives, polyester adhesives, silicone adhesives, epoxy adhesives, and urethane adhesives, and among these, two-component curing urethane adhesives can be preferably used. Examples of solvent-based adhesives include rubber-based adhesives, vinyl-based adhesives, silicone-based adhesives, epoxy-based adhesives, phenol-based adhesives, and olefin-based adhesives.
[0086] In addition, when the substrate has an aluminum vapor deposition film and an adhesive layer is provided adjacent to the vapor deposition film, it is preferable that the adhesive layer is composed of a cured product of a resin composition containing a polyester polyol, an isocyanate compound, and a phosphoric acid-modified compound. When a laminate having a vapor-deposited film is applied to a packaging material, a bending load is applied to the laminate by a molding machine, etc., which may cause cracks in the aluminum vapor-deposited film. By using the specific adhesive as described above, it is possible to suppress a decrease in the oxygen barrier property and water vapor barrier property even if cracks occur in the aluminum vapor-deposited film.
[0087] The polyester polyol has two or more hydroxyl groups as functional groups in one molecule. The isocyanate compound has two or more isocyanate groups as functional groups in one molecule. The polyester polyol has, for example, a polyester structure or a polyester polyurethane structure as a main skeleton.
[0088] As a specific example of a resin composition containing a polyester polyol, an isocyanate compound, and a phosphoric acid-modified compound, the PASLIM series available from DIC Corporation can be used.
[0089] The resin composition may further contain a plate-like inorganic compound, a coupling agent, cyclodextrin and / or a derivative thereof, and the like.
[0090] As the polyester polyol having two or more hydroxyl groups in one molecule as a functional group, for example, the following [First Example] to [Third Example] can be used. [Example 1] Polyester polyol obtained by polycondensation of ortho-oriented polycarboxylic acid or its anhydride with polyhydric alcohol [Example 2] Polyester polyol with glycerol structure [Example 3] Polyester polyol with isocyanuric ring Each polyester polyol will be described below.
[0091] The polyester polyol according to the first example is a polycondensate obtained by polycondensing a polycarboxylic acid component containing at least one or more types of orthophthalic acid and its anhydride, and a polyhydric alcohol component containing at least one type selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, and cyclohexanedimethanol. In particular, polyester polyols in which the content of orthophthalic acid or its anhydride in the total polyvalent carboxylic acid components is 70 to 100 mass % are preferred.
[0092] The polyester polyol according to the first example essentially contains orthophthalic acid and its anhydride as the polycarboxylic acid component, but may be copolymerized with other polycarboxylic acid components as long as the effect of the present embodiment is not impaired. Specifically, the polybasic acids include aliphatic polybasic carboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, and dodecane dicarboxylic acid, unsaturated bond-containing polybasic carboxylic acids such as maleic anhydride, maleic acid, and fumaric acid, alicyclic polybasic carboxylic acids such as 1,3-cyclopentane dicarboxylic acid and 1,4-cyclohexane dicarboxylic acid, aromatic polybasic carboxylic acids such as terephthalic acid, isophthalic acid, pyromellitic acid, trimellitic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyl dicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, anhydrides of these dicarboxylic acids, and ester-forming derivatives of these dicarboxylic acids, p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid, and ester-forming derivatives of these dihydroxycarboxylic acids. Among these, succinic acid, 1,3-cyclopentane dicarboxylic acid, and isophthalic acid are preferred. Two or more of the above other polyvalent carboxylic acids may be used.
[0093] As a polyester polyol according to a second example, a polyester polyol having a glycerol skeleton represented by general formula (1) can be mentioned. [ka] In general formula (1), R1, R2, and R3 each independently represent H (hydrogen atom) or a group represented by the following general formula (2). [ka]
[0094] In formula (2), n represents an integer of 1 to 5, X represents an arylene group selected from the group consisting of 1,2-phenylene groups, 1,2-naphthylene groups, 2,3-naphthylene groups, 2,3-anthraquinonediyl groups, and 2,3-anthracenediyl groups, which may have a substituent, and Y represents an alkylene group having 2 to 6 carbon atoms. However, at least one of R1, R2, and R3 represents a group represented by general formula (2).
[0095] In general formula (1), at least one of R1, R2, and R3 must be a group represented by general formula (2). In particular, it is preferable that all of R1, R2, and R3 are groups represented by general formula (2).
[0096] In addition, the compound may be a mixture of two or more of a compound in which any one of R1, R2, and R3 is a group represented by general formula (2), a compound in which any two of R1, R2, and R3 are groups represented by general formula (2), and a compound in which all of R1, R2, and R3 are groups represented by general formula (2).
[0097] X represents an optionally substituted arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group. When X is substituted, it may be substituted with one or more substituents, and the substituent is attached to any carbon atom on X other than the free radical. The substituents include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, a N-ethylcarbamoyl group, a phenyl group, and a naphthyl group.
[0098] In the general formula (2), Y represents an alkylene group having 2 to 6 carbon atoms, such as an ethylene group, a propylene group, a butylene group, a neopentylene group, a 1,5-pentylene group, a 3-methyl-1,5-pentylene group, a 1,6-hexylene group, a methylpentylene group, or a dimethylbutylene group. Among these, Y is preferably a propylene group or an ethylene group, and most preferably an ethylene group.
[0099] The polyester resin compound having a glycerol skeleton represented by general formula (1) can be synthesized by reacting glycerol, an aromatic polycarboxylic acid or its anhydride in which a carboxylic acid is substituted at the ortho position, and a polyhydric alcohol component as essential components.
[0100] Examples of aromatic polycarboxylic acids or anhydrides in which a carboxylic acid is substituted at the ortho position include orthophthalic acid or anhydride, naphthalene 2,3-dicarboxylic acid or anhydride, naphthalene 1,2-dicarboxylic acid or anhydride, anthraquinone 2,3-dicarboxylic acid or anhydride, and 2,3-anthracene carboxylic acid or anhydride. These compounds may have a substituent at any carbon atom of the aromatic ring, such as a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, or a naphthyl group.
[0101] Examples of the polyhydric alcohol component include alkylene diols having 2 to 6 carbon atoms, such as ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, and dimethylbutanediol.
[0102] The polyester polyol according to the third example is a polyester polyol having an isocyanuric ring represented by the following general formula (3). [ka] In the general formula (3), R1, R2, and R3 each independently represent "-(CH2)n1-OH (wherein n1 represents an integer of 2 to 4)" or a structure represented by the general formula (4). [ka]
[0103] In the general formula (4), n2 represents an integer of 2 to 4, n3 represents an integer of 1 to 5, X represents an arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group, which may have a substituent, and Y represents an alkylene group having 2 to 6 carbon atoms. However, at least one of R1, R2, and R3 is a group represented by the general formula (4).
[0104] In the general formula (3), the alkylene group represented by -(CH2)n1- may be linear or branched. Among them, n1 is preferably 2 or 3, and most preferably 2.
[0105] In the general formula (4), n2 represents an integer of 2 to 4; n3 represents an integer of 1 to 5. X represents an optionally substituted arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group.
[0106] When X is substituted, it may be substituted with one or more substituents, and the substituent is attached to any carbon atom on X other than the free radical. The substituents include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, a N-ethylcarbamoyl group, a phenyl group, and a naphthyl group. The substituent for X is preferably a hydroxyl group, a cyano group, a nitro group, an amino group, a phthalimido group, a carbamoyl group, an N-ethylcarbamoyl group, or a phenyl group, and most preferably a hydroxyl group, a phenoxy group, a cyano group, a nitro group, a phthalimido group, or a phenyl group.
[0107] In the general formula (4), Y represents an alkylene group having 2 to 6 carbon atoms, such as an ethylene group, a propylene group, a butylene group, a neopentylene group, a 1,5-pentylene group, a 3-methyl-1,5-pentylene group, a 1,6-hexylene group, a methylpentylene group, or a dimethylbutylene group. Among these, Y is preferably a propylene group or an ethylene group, and most preferably an ethylene group.
[0108] In general formula (3), at least one of R1, R2, and R3 is a group represented by general formula (4). Of these, it is preferable that all of R1, R2, and R3 are groups represented by general formula (4).
[0109] In addition, the compound may be a mixture of two or more of a compound in which any one of R1, R2, and R3 is a group represented by general formula (4), a compound in which any two of R1, R2, and R3 are groups represented by general formula (4), and a compound in which all of R1, R2, and R3 are groups represented by general formula (4).
[0110] The polyester polyol having an isocyanuric ring represented by the general formula (3) can be synthesized by reacting a triol having an isocyanuric ring, an aromatic polycarboxylic acid or its anhydride in which a carboxylic acid is substituted at the ortho position, and a polyhydric alcohol component as essential components.
[0111] Examples of triols having an isocyanuric ring include alkylene oxide adducts of isocyanuric acid such as 1,3,5-tris(2-hydroxyethyl)isocyanuric acid and 1,3,5-tris(2-hydroxypropyl)isocyanuric acid.
[0112] Examples of aromatic polycarboxylic acids or anhydrides in which a carboxylic acid is substituted at the ortho position include orthophthalic acid or anhydride, naphthalene 2,3-dicarboxylic acid or anhydride, naphthalene 1,2-dicarboxylic acid or anhydride, anthraquinone 2,3-dicarboxylic acid or anhydride, and 2,3-anthracene carboxylic acid or anhydride, etc. These compounds may have a substituent on any carbon atom of the aromatic ring.
[0113] Examples of the substituent include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, and a naphthyl group.
[0114] The polyhydric alcohol component may be an alkylene diol having 2 to 6 carbon atoms, such as ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, or dimethylbutanediol. Among these, polyester polyol compounds having an isocyanuric ring, which use 1,3,5-tris(2-hydroxyethyl)isocyanuric acid or 1,3,5-tris(2-hydroxypropyl)isocyanuric acid as a triol compound having an isocyanuric ring, orthophthalic anhydride as an aromatic polycarboxylic acid or its anhydride in which a carboxylic acid is substituted at the ortho position, and ethylene glycol as a polyhydric alcohol, are particularly excellent in oxygen barrier properties and adhesion and are therefore preferred.
[0115] The isocyanuric ring is highly polar and trifunctional, and can increase the polarity of the entire system and increase the crosslink density. From this viewpoint, it is preferable that the adhesive resin contains 5% by mass or more of the isocyanuric ring based on the total solid content of the adhesive resin.
[0116] The isocyanate compound has two or more isocyanate groups in the molecule. The isocyanate compound may be either aromatic or aliphatic, and may be either a low molecular weight compound or a high molecular weight compound. Furthermore, the isocyanate compound may be a blocked isocyanate compound obtained by subjecting a known isocyanate blocking agent to an addition reaction by a known, conventional appropriate method. Among these, from the viewpoints of adhesiveness and retort resistance, polyisocyanate compounds having three or more isocyanate groups are preferred, and from the viewpoints of oxygen barrier property and water vapor barrier property, aromatic compounds are preferred.
[0117] Specific examples of the isocyanate compound include tetramethylene diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, metaxylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, and trimers of these isocyanate compounds, as well as adducts, biurets, and allophanates obtained by reacting these isocyanate compounds with low-molecular-weight active hydrogen compounds or their alkylene oxide adducts, or high-molecular-weight active hydrogen compounds. Examples of low molecular weight active hydrogen compounds include ethylene glycol, propylene glycol, metaxylylene alcohol, 1,3-bishydroxyethylbenzene, 1,4-bishydroxyethylbenzene, trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine, and metaxylylenediamine. Examples of molecular weight active hydrogen compounds include polymeric active hydrogen compounds such as various polyester resins, polyether polyols, and polyamides.
[0118] The phosphoric acid-modified compound is, for example, a compound represented by the following general formula (5) or (6). [ka] In general formula (5), R1, R2, and R3 are groups selected from a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, a (meth)acryloyl group, a phenyl group which may have a substituent, and an alkyl group having 1 to 4 carbon atoms which has a (meth)acryloyloxy group, at least one of which is a hydrogen atom, and n is an integer of 1 to 4. [ka] In the formula, R4 and R5 are groups selected from a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, a (meth)acryloyl group, a phenyl group which may have a substituent, and an alkyl group having 1 to 4 carbon atoms and having a (meth)acryloyloxy group, n is an integer of 1 to 4, x is an integer of 0 to 30, and y is an integer of 0 to 30, except for the case where both x and y are 0.
[0119] More specific examples include phosphoric acid, pyrophosphoric acid, triphosphoric acid, methyl acid phosphate, ethyl acid phosphate, butyl acid phosphate, dibutyl phosphate, 2-ethylhexyl acid phosphate, bis(2-ethylhexyl) phosphate, isododecyl acid phosphate, butoxyethyl acid phosphate, oleyl acid phosphate, tetracosyl acid phosphate, 2-hydroxyethyl methacrylate acid phosphate, and polyoxyethylene alkyl ether phosphate, and one or more of these can be used.
[0120] The content of the phosphoric acid-modified compound in the resin composition is preferably from 0.005% by mass to 10% by mass, and more preferably from 0.01% by mass to 1% by mass. By making the content of the phosphoric acid-modified compound 0.005% by mass or more, the oxygen barrier property and water vapor barrier property of the laminate of the present invention can be improved, and by making the content of the phosphoric acid-modified compound 10% by mass or less, the adhesiveness of the adhesive layer can be improved.
[0121] The resin composition containing the polyester polyol, the isocyanate compound and the phosphoric acid-modified compound may contain a plate-like inorganic compound, which can improve the adhesiveness of the adhesive layer and the bending load resistance of the laminate of the present invention. Examples of the plate-like inorganic compounds include kaolinite-serpentine group clay minerals (such as halloysite, kaolinite, endelite, dickite, nacrite, antigorite, and chrysotile) and pyrophyllite-talc group (such as pyrophyllite, talc, and keroli).
[0122] Examples of the coupling agent include silane-based coupling agents, titanium-based coupling agents, and aluminum-based coupling agents represented by the following general formula (7). These coupling agents may be used alone or in combination of two or more kinds. [ka]
[0123] Examples of silane coupling agents include vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-methacryloxytrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropyltriethoxysilane, N-β( aminoethyl) γ-aminopropyl methyl dimethoxysilane, N-β (aminoethyl) γ-aminopropyl trimethoxysilane, N-β (aminoethyl) γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, γ-chloropropyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, 3-isocyanatopropyl triethoxysilane, 3-acryloxypropyl trimethoxysilane and 3-triethoxysilyl-N-(1,3-dimethyl-butylidene).
[0124] Examples of titanium-based coupling agents include isopropyl triisostearoyl titanate, isopropyl tri(N-aminoethyl-aminoethyl) titanate, isopropyl tridodecylbenzenesulfonyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, tetraoctyl bis(didodecyl phosphite) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, bis(dioctyl pyrophosphate)ethylene titanate, isopropyl trioctyl nor titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl isostearoyl diacryl titanate, diisostearoyl ethylene titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl tricumyl phenyl titanate, and dicumyl phenyl oxyacetate titanate.
[0125] Specific examples of aluminum-based coupling agents include acetoalkoxyaluminum diisopropylate, diisopropoxyaluminum ethyl acetoacetate, diisopropoxyaluminum monomethacrylate, isopropoxyaluminum alkyl acetoacetate mono(dioctyl phosphate), aluminum 2-ethylhexanoate oxide trimer, aluminum stearate oxide trimer, and alkyl acetoacetate aluminum oxide trimer.
[0126] The resin composition may contain cyclodextrin and / or a derivative thereof, which can improve the adhesiveness of the adhesive layer and can further improve the bending load resistance of the laminate of the present invention. Specifically, for example, cyclodextrin, alkylated cyclodextrin, acetylated cyclodextrin, hydroxyalkylated cyclodextrin, and other cyclodextrins in which the hydrogen atom of the hydroxyl group of the glucose unit of cyclodextrin is substituted with another functional group can be used. Branched cyclic dextrins can also be used. Furthermore, the cyclodextrin skeleton in cyclodextrin and cyclodextrin derivatives may be any of α-cyclodextrin consisting of six glucose units, β-cyclodextrin consisting of seven glucose units, and γ-cyclodextrin consisting of eight glucose units. These compounds may be used alone or in combination of two or more. Hereinafter, these cyclodextrins and / or their derivatives may be collectively referred to as dextrin compounds.
[0127] From the viewpoint of compatibility and dispersibility in the resin composition, it is preferable to use a cyclodextrin derivative as the cyclodextrin compound.
[0128] Examples of alkylated cyclodextrins include methyl-α-cyclodextrin, methyl-β-cyclodextrin, and methyl-γ-cyclodextrin. These compounds may be used alone or in combination of two or more.
[0129] Examples of acetylated cyclodextrin include monoacetyl-α-cyclodextrin, monoacetyl-β-cyclodextrin, and monoacetyl-γ-cyclodextrin. These compounds may be used alone or in combination of two or more.
[0130] Examples of hydroxyalkylated cyclodextrins include hydroxypropyl-α-cyclodextrin, hydroxypropyl-β-cyclodextrin, and hydroxypropyl-γ-cyclodextrin, etc. These compounds may be used alone or in combination of two or more kinds.
[0131] The thickness of the adhesive layer is preferably 0.5 μm or more and 6 μm or less, more preferably 0.8 μm or more and 5 μm or less, and even more preferably 1 μm or more and 4.5 μm or less. By making the thickness of the adhesive layer 0.5 μm or more, the adhesiveness of the adhesive layer can be improved. In addition, when an adhesive layer made of a cured product of a resin composition containing a polyester polyol, an isocyanate compound, and a phosphoric acid-modified compound is provided adjacent to an aluminum vapor deposition film, the bending load resistance of the laminate can be improved. By setting the thickness of the adhesive layer to 6 μm or less, the processability of the laminate can be improved.
[0132] Alternatively, the heat seal layer can be formed by extruding a resin material containing polyethylene onto the substrate or onto an intermediate layer having a vapor-deposited film, and then drying the extrusion.
[0133] <Intermediate layer with evaporated film> In the first embodiment, the laminate can have an intermediate layer between the substrate and the heat seal layer, the intermediate layer having a vapor deposition film on at least one side. The intermediate layer is made of polyethylene, like the substrate and the heat seal layer, and this can improve the recyclability of the laminate. This can also further improve the gas barrier properties of the laminate according to the present invention.
[0134] The intermediate layer having the vapor-deposited film may be composed of a stretched film or an unstretched film, but is preferably a stretched film from the viewpoint of printability, strength, and heat resistance of the laminate. Also, it may be uniaxially stretched or biaxially stretched, but is preferably a biaxially stretched film from the viewpoint of strength.
[0135] The intermediate layer having a vapor-deposited film contains at least one of high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and a copolymer of ethylene and other monomers. Among these, from the viewpoints of printability, strength, and heat resistance, high density polyethylene (HDPE) and medium density polyethylene (MDPE) are preferred, and high density polyethylene (HDPE) is more preferred. From the viewpoint of environmental load, these polyethylenes are preferably derived from biomass.
[0136] The polyethylene content in the intermediate layer comprising a vapor-deposited film is preferably 50% by mass or more, and more preferably 70% by mass or more.
[0137] The intermediate layer comprising a vapor-deposited film may contain additives within the range that does not impair the characteristics of the present invention. Examples of such additives include crosslinking agents, antioxidants, ultraviolet absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.
[0138] The above-mentioned metals and metal oxides can be used as materials for forming the vapor-deposited film, but from the viewpoints of gas barrier properties and cost, it is preferable to form the vapor-deposited film from aluminum. Furthermore, the use of aluminum can impart luster and improve the design.
[0139] From the viewpoints of productivity and economy, the thickness of the intermediate layer including the vapor-deposited film is preferably 9 μm or more and 50 μm or less, and more preferably 12 μm or more and 30 μm or less. The thickness of the vapor-deposited film is preferably 0.002 μm or more and 0.4 μm or less, and more preferably 0.005 μm or more and 0.1 μm or less. By setting the thickness of the vapor-deposited film within the above numerical range, it is possible to prevent the occurrence of cracks in the vapor-deposited film while maintaining the gas barrier properties.
[0140] The intermediate layer having a vapor-deposited film may have an image formed on its surface. The image forming method is as described above.
[0141] The intermediate layer having a vapor-deposited film can be formed by forming a polyethylene film by melt extrusion molding such as inflation molding or T-die molding from a resin material containing polyethylene, forming a vapor-deposited film on at least one surface of the polyethylene film by the above-mentioned method, and then laminating the film on a substrate via an adhesive. In this case, the polyethylene film may be subjected to a stretching treatment before vapor deposition or lamination. Alternatively, an intermediate layer having a vapor-deposited film can be formed by extruding a resin material containing polyethylene onto a substrate, drying the extruded resin material, and then forming a vapor-deposited film.
[0142] <Laminate of the Second Aspect> As shown in FIG. 3, the laminate 10 of the second embodiment comprises a substrate 20, an intermediate layer 50 having a vapor-deposited film 40 on at least one surface thereof, and a heat seal layer 30. Each layer of the laminate will now be described.
[0143] <Base material> The substrate is stretched, and may be uniaxially or biaxially stretched, but is preferably biaxially stretched from the viewpoint of strength. The preferred stretch ratios in the longitudinal and transverse directions are the same as those in the first embodiment.
[0144] The substrate contains at least one of high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and a copolymer of ethylene and other monomers. Among these, high density polyethylene (HDPE) and medium density polyethylene (MDPE) are preferred from the viewpoints of printability, strength, and heat resistance, and medium density polyethylene is more preferred from the viewpoint of stretchability. From the viewpoint of environmental load, these polyethylenes are preferably derived from biomass.
[0145] The content of polyethylene in the substrate is preferably 50% by mass or more, and more preferably 70% by mass or more.
[0146] The substrate may contain additives within the range that does not impair the characteristics of the present invention. For example, crosslinking agents, antioxidants, ultraviolet absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, modifying resins, etc. may be mentioned.
[0147] In one embodiment, the substrate has a multi-layer structure, the details of which are described above.
[0148] The thickness of the substrate is preferably 9 μm or more and 50 μm or less, and more preferably 12 μm or more and 30 μm or less. By setting the thickness of the substrate within the above numerical range, the printability, strength, and heat resistance of the laminate can be further improved.
[0149] The substrate may have an image formed on its surface. It is preferable to form the image on the side of the substrate where the heat seal layer is laminated, since this can prevent deterioration of the image over time. The method for forming the image is as described in the first embodiment, and from the viewpoint of environmental load, flexographic printing is preferred.
[0150] The method for preparing the substrate is as described in the first embodiment.
[0151] <Intermediate layer with evaporated film> In a second embodiment, the laminate comprises an intermediate layer between the substrate and the heat seal layer, the intermediate layer having a vapor deposition film on at least one surface thereof. This intermediate layer, like the substrate and the heat seal layer, is made of polyethylene, which can improve the recyclability of the laminate.
[0152] The intermediate layer having the vapor-deposited film may be composed of a stretched film or an unstretched film, but is preferably a stretched film from the viewpoint of printability, strength, and heat resistance of the laminate. In addition, it may be uniaxially stretched or biaxially stretched, but is preferably a biaxially stretched film from the viewpoint of strength.
[0153] The intermediate layer having a vapor-deposited film contains at least one of high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and a copolymer of ethylene and other monomers. Among these, high density polyethylene (HDPE) and medium density polyethylene (MDPE) are preferred from the viewpoints of printability, strength, and heat resistance, and medium density polyethylene is more preferred from the viewpoint of stretchability. From the viewpoint of environmental load, these polyethylenes are preferably derived from biomass.
[0154] The polyethylene content in the intermediate layer comprising a vapor-deposited film is preferably 50% by mass or more, and more preferably 70% by mass or more.
[0155] The intermediate layer comprising a vapor-deposited film may contain additives within the range that does not impair the characteristics of the present invention. Examples of such additives include crosslinking agents, antioxidants, ultraviolet absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.
[0156] As the material for forming the vapor-deposited film, the above-mentioned materials can be used, but from the viewpoint of gas barrier properties, it is preferable to form the vapor-deposited film from aluminum.
[0157] From the viewpoints of productivity and economy, the thickness of the intermediate layer including the vapor-deposited film is preferably 9 μm or more and 50 μm or less, and more preferably 12 μm or more and 30 μm or less. The thickness of the vapor-deposited film is preferably 0.002 μm or more and 0.4 μm or less, and more preferably 0.005 μm or more and 0.1 μm or less. By setting the thickness of the vapor-deposited film within the above numerical range, it is possible to prevent the occurrence of cracks in the vapor-deposited film while maintaining the gas barrier properties.
[0158] The intermediate layer having a vapor-deposited film may have an image formed on its surface. The image forming method is the same as that described in the first embodiment.
[0159] The method for producing the intermediate layer having a vapor-deposited film is as described in the first embodiment.
[0160] <Heat seal layer> The heat seal layer contains at least one of high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), and a copolymer of ethylene and other monomers. Among these, low density polyethylene (LDPE) and linear low density polyethylene (LLDPE) are preferred from the viewpoint of heat sealability. From the viewpoint of environmental load, these polyethylenes are preferably derived from biomass.
[0161] The content of polyethylene in the heat seal layer is preferably 50% by mass or more, and more preferably 70% by mass or more.
[0162] The heat seal layer may contain additives within the range that does not impair the characteristics of the present invention. For example, crosslinking agents, antioxidants, ultraviolet absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, modifying resins, etc. may be included.
[0163] The thickness of the heat seal layer is preferably 20 μm or more and 200 μm or less, and more preferably 30 μm or more and 150 μm or less. By setting the thickness of the heat seal layer within the above numerical range, the heat sealability can be improved.
[0164] The method for producing the heat seal layer is as described in the first embodiment.
[0165] <Packaging materials> In one embodiment, the packaging material according to the present invention can be produced by folding the laminate in half, overlapping it so that the heat seal layer of the laminate is on the inside, and heat sealing the ends. Alternatively, the laminate can be produced by overlapping two sheets of the laminate with their heat seal layers facing each other and heat sealing the ends thereof. Depending on the sealing method, for example, a side seal type, a two-sided seal type, a three-sided seal type, a four-sided seal type, an envelope seal type, a grommet seal type (pillow seal type), a pleated seal type, a flat bottom seal type, a square bottom seal type, a gusset type, and other heat seal forms can be used to produce packaging materials in various forms. In addition, for example, a self-supporting packaging bag (standing pouch) can also be used. Heat sealing can be performed by a known method such as bar sealing, rotary roll sealing, belt sealing, impulse sealing, high frequency sealing, ultrasonic sealing, etc.
[0166] The laminate of the present invention, even if it is made of only one type of resin (i.e., polyethylene), has a base material that satisfies the strength and printability required for an outer film of a packaging material, and the heat seal layer enables packaging, so it is extremely suitable as a material for constituting packaging materials that require recyclability. EXAMPLES
[0167] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples.
[0168] <Example 1> Medium density polyethylene (density: 0.941 g / cm 3A polyethylene film having a thickness of 100 μm was formed from a polyethylene terephthalate copolymer having a melting point of 129° C., MFR of 1.3 g / 10 min, manufactured by Dow Chemical Co., trade name: Elite 5538G) by an inflation molding method. This polyethylene film was stretched in the machine direction (MD) at a stretching ratio of 5 times to obtain a substrate having a thickness of 20 μm.
[0169] A vapor-deposited film made of aluminum oxide having a thickness of 0.1 μm was formed on one surface of the substrate by vacuum vapor deposition.
[0170] A 40 μm-thick unstretched linear low-density polyethylene (LLDPE) film (manufactured by Toyobo Co., Ltd., product name: L6100) was laminated onto the vapor-deposited surface of the substrate via a two-component curing urethane adhesive (manufactured by Rock Paint Co., Ltd., product name: RU-77T / H-7) to obtain a laminate.
[0171] <Example 2> High density polyethylene (density: 0.961g / cm 3 , melting point 135°C, MFR: 0.7g / 10min, ExxonMobil, trade name: HTA108) and medium density polyethylene (density: 0.941g / cm 3 A polyethylene film consisting of a high density polyethylene layer, a medium density polyethylene layer and a high density polyethylene layer was produced by forming a film from a polyethylene terephthalate (Elite5538G, melting point 129°C, MFR: 1.3g / 10min, manufactured by Dow Chemical) by inflation molding. The high density polyethylene layer had a thickness of 20μm, and the medium density polyethylene layer had a thickness of 60μm. This polyethylene film was stretched in the machine direction (MD) at a stretching ratio of 5 times to obtain a substrate having a thickness of 20 μm.
[0172] A vapor-deposited film made of aluminum oxide having a thickness of 0.1 μm was formed on one surface of the substrate by vacuum vapor deposition.
[0173] A 40 μm-thick unstretched linear low-density polyethylene (LLDPE) film (manufactured by Toyobo Co., Ltd., product name: L6100) was laminated onto the non-vapor-deposited surface of the substrate via a two-component curing urethane adhesive (manufactured by Rock Paint Co., Ltd., product name: RU-77T / H-7) to obtain a laminate.
[0174] <Example 3> Medium density polyethylene (density: 0.941 g / cm 3 A polyethylene film having a thickness of 100 μm was formed from a polyethylene terephthalate (manufactured by Dow Chemical under the trade name of Elite 5538G, melting point 129° C., MFR: 1.3 g / 10 min) by inflation molding. Two polyethylene films were stretched in the machine direction (MD) at a stretching ratio of 5 times to obtain a stretched polyethylene film with a thickness of 20 μm.
[0175] A vapor-deposited aluminum film having a thickness of 0.1 μm was formed on one surface of a sheet of stretched polyethylene film by vacuum deposition.
[0176] Next, another stretched polyethylene film was laminated onto the vapor-deposited surface of the stretched polyethylene film having the vapor-deposited film thereon via a two-component curing urethane adhesive (manufactured by Rock Paint Co., Ltd., product name: RU-77T / H-7).
[0177] A 40 μm-thick unstretched linear low-density polyethylene (LLDPE) film (manufactured by Toyobo Co., Ltd., product name: L6100) was laminated onto the non-vapor-deposited surface of the stretched polyethylene film with the vapor-deposited film, via a two-component curing urethane adhesive (manufactured by Rock Paint Co., Ltd., product name: RU-77T / H-7), to obtain a laminate.
[0178] <Example 4> Medium density polyethylene (density: 0.941 g / cm3, melting point: 129°C, MFR: 1.3 g / 10 min, Dow Chemical, product name: Elite5538G) was formed into a film by inflation molding to obtain a polyethylene film having a thickness of 100 µm. This polyethylene film was stretched in the machine direction (MD) at a stretching ratio of 2.24 times, and in the transverse direction (TD) at a stretching ratio of 2.24 times to obtain a substrate having a thickness of 20 μm.
[0179] A vapor-deposited film made of aluminum oxide having a thickness of 0.1 μm was formed on one surface of the substrate by vacuum vapor deposition.
[0180] A 40 μm-thick unstretched linear low-density polyethylene (LLDPE) film (manufactured by Toyobo Co., Ltd., product name: L6100) was laminated onto the vapor-deposited surface of the substrate via a two-component curing urethane adhesive (manufactured by Rock Paint Co., Ltd., product name: RU-77T / H-7) to obtain a laminate.
[0181] <Example 5> High density polyethylene (density: 0.960g / cm 3 , melting point 130°C, MFR: 0.85g / 10min, Dowchemical Co., trade name: Elite5960) The above high-density polyethylene and medium-density polyethylene (density: 0.940 g / cm 3 , melting point 126°C, MFR: 0.85g / 10min, Dowchemical Co., product name Elite5940) blend resin (mass ratio 4:6), The medium density polyethylene, Ultra-low density polyethylene (density 0.870 g / cm3, melting point 55°C, MFR: 1.0 g / 10 min, manufactured by Dowchemical, product name: Affinity EG8100G) was extruded by inflation molding into a tubular film having, from the outside, a high-density polyethylene layer (12.5 μm), a blend resin layer of high-density polyethylene and medium-density polyethylene (12.5 μm), a medium-density polyethylene layer (31.25 μm), and an ultra-low-density polyethylene layer (6.25 μm).The inner ultra-low-density polyethylene layers were then pressed together using a rubber roll to obtain a polyethylene film having a thickness of 125 μm and having a high-density polyethylene layer (12.5 μm), blend resin layer (12.5 μm), medium-density polyethylene layer (31.25 μm), ultra-low-density polyethylene layer (12.5 μm), medium-density polyethylene layer (31.25 μm), and blend resin layer (12.5 μm).
[0182] This polyethylene film was stretched in the machine direction (MD) at a stretch ratio of 5 times to obtain a substrate having a thickness of 25 μm. A vapor-deposited film made of aluminum oxide having a thickness of 0.1 μm was formed on one surface of the substrate by vacuum vapor deposition.
[0183] A 40 μm-thick unstretched linear low-density polyethylene (LLDPE) film (manufactured by Toyobo Co., Ltd., product name: L6100) was laminated onto the vapor-deposited surface of the substrate via a two-component curing urethane adhesive (manufactured by Rock Paint Co., Ltd., product name: RU-77T / H-7) to obtain a laminate.
[0184] <Example 6> High density polyethylene (density: 0.960 g / cm3, melting point: 130°C, MFR: 0.85 g / 10 min, Dowchemical, product name: Elite5960), Medium density polyethylene (density: 0.940 g / cm3, melting point: 126°C, MFR: 0.85 g / 10 min, Dowchemical, product name: Elite5940), Ultra-low density polyethylene (density: 0.870 g / cm3, melting point: 55°C, MFR: 1.0 g / 10 min, Dow Chemical, product name: Affinity EG8100G) was extruded by inflation molding into a tubular film having a high density polyethylene layer (12.5 μm), a medium density polyethylene layer (43.75 μm), and an ultra-low density polyethylene layer (6.25 μm) from the outside, and the inner ultra-low density polyethylene layers were then pressed together using a rubber roll to obtain a 125 μm thick polyethylene film having a high density polyethylene layer (12.5 μm), a medium density polyethylene layer (43.75 μm), an ultra-low density polyethylene layer (12.5 μm), a medium density polyethylene layer (43.75 μm), and a high density polyethylene layer (12.5 μm). This polyethylene film was stretched in the machine direction (MD) at a stretching ratio of 5 times to obtain a substrate having a thickness of 25 μm.
[0185] A vapor-deposited film made of aluminum oxide having a thickness of 0.1 μm was formed on one surface of the substrate by vacuum vapor deposition.
[0186] A 40 μm-thick unstretched linear low-density polyethylene (LLDPE) film (manufactured by Toyobo Co., Ltd., product name: L6100) was laminated onto the vapor-deposited surface of the substrate via a two-component curing urethane adhesive (manufactured by Rock Paint Co., Ltd., product name: RU-77T / H-7) to obtain a laminate.
[0187] <Comparative Example 1> Medium density polyethylene (density: 0.941 g / cm 3 A polyethylene film having a thickness of 20 μm was formed from a polyethylene terephthalate copolymer having a melting point of 129° C., MFR of 1.3 g / 10 min, manufactured by Dow Chemical Co., trade name: Elite 5538G) by an inflation molding method.
[0188] A vapor-deposited film of aluminum oxide having a thickness of 0.1 μm was formed on one surface of a polyethylene film by vacuum deposition.
[0189] A 40 μm-thick unstretched linear low-density polyethylene (LLDPE) film (manufactured by Toyobo Co., Ltd., product name: L6100) was laminated onto the non-vapor-deposited surface of the polyethylene film via a two-component curing urethane adhesive (manufactured by Rock Paint Co., Ltd., product name: RU-77T / H-7) to obtain a laminate.
[0190] <Comparative Example 2> High density polyethylene (density: 0.961g / cm 3 , melting point 135°C, MFR: 0.7g / 10min, ExxonMobil, trade name: HTA108) and medium density polyethylene (density: 0.941g / cm 3 A polyethylene film consisting of a high density polyethylene layer, a medium density polyethylene layer and a high density polyethylene layer was produced by forming a film from a polyethylene terephthalate (Elite5538G, melting point 129°C, MFR: 1.3g / 10min, manufactured by Dow Chemical) by inflation molding. The high density polyethylene layer had a thickness of 4μm, and the medium density polyethylene layer had a thickness of 12μm.
[0191] A vapor-deposited film of aluminum oxide having a thickness of 0.1 μm was formed on one surface of a polyethylene film by vacuum deposition.
[0192] A 40 μm-thick unstretched linear low-density polyethylene (LLDPE) film (manufactured by Toyobo Co., Ltd., product name: L6100) was laminated onto the non-vapor-deposited surface of the polyethylene film using a two-component curing urethane adhesive (manufactured by Rock Paint Co., Ltd., product name: RU-77T / H-7) to obtain a laminate.
[0193] <Comparative Example 3> Medium density polyethylene (density: 0.941 g / cm 3 A polyethylene film having a thickness of 20 μm was formed from a polyethylene terephthalate (manufactured by Dow Chemical under the trade name of Elite 5538G, melting point 129° C., MFR: 1.3 g / 10 min) by inflation molding.
[0194] A vapor-deposited aluminum film having a thickness of 0.1 μm was formed on one surface of a polyethylene film by vacuum deposition.
[0195] Next, another polyethylene film was laminated onto the vapor-deposited surface of the polyethylene film having the vapor-deposited film thereon via a two-component curing urethane adhesive (manufactured by Rock Paint Co., Ltd., product name: RU-77T / H-7).
[0196] A 40 μm-thick unstretched linear low-density polyethylene (LLDPE) film (manufactured by Toyobo Co., Ltd., product name: L6100) was laminated onto the non-vapor-deposited surface of the polyethylene film with the vapor-deposited film, via a two-component curing urethane adhesive (manufactured by Rock Paint Co., Ltd., product name: RU-77T / H-7), to obtain a laminate.
[0197] <Comparative Example 4> High density polyethylene (density: 0.960 g / cm3, melting point: 130°C, MFR: 0.85 g / 10 min, Dowchemical, product name: Elite5960), Medium density polyethylene (density: 0.940 g / cm3, melting point: 126°C, MFR: 0.85 g / 10 min, Dowchemical, product name: Elite5940), Ultra-low density polyethylene (density: 0.870 g / cm3, melting point: 55°C, MFR: 1.0 g / 10 min, Dow Chemical, product name: Affinity EG8100G) was extruded by inflation molding into a tubular film having a high-density polyethylene layer, a medium-density polyethylene layer, and an ultra-low-density polyethylene layer from the outside, and the inner ultra-low-density polyethylene layers were then pressed together using a rubber roll to obtain a 25 μm-thick polyethylene film having a high-density polyethylene layer (2.5 μm), a medium-density polyethylene layer (8.75 μm), an ultra-low-density polyethylene layer (2.5 μm), a medium-density polyethylene layer (8.75 μm), and a high-density polyethylene layer (2.5 μm).
[0198] A laminate was produced in the same manner as in Example 6, except that the substrate was changed to the polyethylene film produced as described above.
[0199] <Printability evaluation> An image was formed on one side of the substrate and polyethylene film prepared in the above Examples and Comparative Examples by flexographic printing using a water-based flexographic ink (manufactured by Toyo Ink Mfg. Co., Ltd., product name: Aquariona). The formed image was visually observed, and the printability of the substrate and polyethylene film was evaluated based on the following evaluation criteria. The evaluation results are summarized in Table 1. (Evaluation Criteria) ◯: The dimensional stability during printing was good, and good images without rubbing, bleeding, etc. could be formed. ×: The film expanded and contracted during printing, causing rubbing and bleeding in the formed image.
[0200] <Rigidity evaluation> The substrates and polyethylene films prepared in the above examples and comparative examples were cut into test pieces with a width of 15 mm, and their stiffness was measured using a loop stiffness measuring tester (manufactured by Toyo Seiki Seisakusho, product name: Loop Stiffness Tester). The length of the loop was 60 mm. The measurement results are summarized in Table 1.
[0201] <Strength evaluation> The substrates and polyethylene films prepared in the above examples and comparative examples were used to prepare dumbbell-shaped test pieces having a width of 10 mm. The tensile strength of the test pieces in the MD direction was measured using a tensile tester (manufactured by Orientec Co., Ltd., RTC-1310A). The chuck distance was 10 mm, and the pulling speed was 300 mm / min. The measurement results are summarized in Table 1.
[0202] <Gas barrier property evaluation> The water vapor permeability (g / m 2 ·day) was measured using a water vapor transmission rate measuring device (PERMATRAN) manufactured by MOCON, USA. The measurement results are summarized in Table 1.
[0203] [Table 1] [Explanation of symbols]
[0204] 10: Laminate 20: Base material 30: Heat seal layer 40: Evaporation film 50: Intermediate layer with vapor deposition film
Claims
1. The film includes at least a substrate and a heat seal layer, The substrate and the heat seal layer are made of polyethylene, The substrate is subjected to a stretching treatment, The substrate has a vapor-deposited film on at least one surface thereof, A laminate, wherein the stretch ratio of the substrate in the longitudinal direction (MD) is 2 times or more and 10 times or less.
2. The laminate according to claim 1 , wherein the vapor-deposited film on the substrate contains aluminum oxide.
3. The laminate according to claim 1 or 2, further comprising an intermediate layer between the substrate and the heat seal layer, the intermediate layer being made of polyethylene and having a vapor deposition film on at least one surface thereof.
4. 4. The laminate according to claim 3, wherein the intermediate layer having the vapor-deposited film is made of a stretched polyethylene film and a vapor-deposited film.
5. The laminate of any one of claims 1 to 4, wherein the substrate comprises at least one of high density polyethylene (HDPE) and medium density polyethylene (MDPE).
6. The laminate according to any one of claims 1 to 5, wherein the substrate has a thickness of 9 µm or more and 50 µm or less.
7. The laminate according to any one of claims 1 to 6, wherein the substrate has a configuration consisting of a high density polyethylene layer, a medium density polyethylene layer, and a high density polyethylene layer.
8. The laminate according to any one of claims 1 to 6, wherein the substrate is a five-layer co-extruded film consisting of a high-density polyethylene layer, a medium-density polyethylene layer, a low-density polyethylene layer, a linear low-density polyethylene layer or a very low-density polyethylene layer, a medium-density polyethylene layer, and a high-density polyethylene layer.
9. The laminate according to any one of claims 1 to 6, wherein the substrate is a seven-layer co-extruded film consisting of a high-density polyethylene layer, a blend resin layer of high-density polyethylene and medium-density polyethylene, a medium-density polyethylene layer, a low-density polyethylene layer, a linear low-density polyethylene layer or a very low-density polyethylene layer, a medium-density polyethylene layer, a blend resin layer of high-density polyethylene and medium-density polyethylene, and a high-density polyethylene layer.
10. The laminate of any one of claims 1 to 9, wherein the heat seal layer comprises at least one of low density polyethylene (LDPE) and linear low density polyethylene (LLDPE).
11. A substrate, an intermediate layer, and a heat seal layer are provided. the substrate, the intermediate layer and the heat seal layer are made of polyethylene; the intermediate layer has a vapor-deposited film on at least one surface, The substrate is subjected to a stretching treatment, A laminate, wherein the stretch ratio of the substrate in the longitudinal direction (MD) is 2 times or more and 10 times or less.
12. 12. The laminate of claim 11, wherein the vapor-deposited film of the polyethylene layer comprises aluminum.
13. 13. The laminate according to claim 11 or 12, wherein the polyethylene layer having the vapor-deposited film comprises a stretched polyethylene film and a vapor-deposited film.
14. The laminate of any one of claims 11 to 13, wherein the substrate comprises at least one of high density polyethylene (HDPE) and medium density polyethylene (MDPE).
15. The laminate according to any one of claims 11 to 14, wherein the substrate has a thickness of 9 µm or more and 50 µm or less.
16. The laminate according to any one of claims 11 to 15, wherein the substrate has a configuration consisting of a high density polyethylene layer, a medium density polyethylene layer, and a high density polyethylene layer.
17. The laminate according to any one of claims 11 to 15, wherein the substrate is a five-layer co-extruded film consisting of a high-density polyethylene layer, a medium-density polyethylene layer, a low-density polyethylene layer, a linear low-density polyethylene layer or a very low-density polyethylene layer, a medium-density polyethylene layer, and a high-density polyethylene layer.
18. The laminate according to any one of claims 11 to 15, wherein the substrate is a seven-layer co-extruded film consisting of a high-density polyethylene layer, a blend resin layer of high-density polyethylene and medium-density polyethylene, a medium-density polyethylene layer, a low-density polyethylene layer, a linear low-density polyethylene layer or a very low-density polyethylene layer, a medium-density polyethylene layer, a blend resin layer of high-density polyethylene and medium-density polyethylene, and a high-density polyethylene layer.
19. The laminate of any one of claims 11 to 18, wherein the heat seal layer comprises at least one of low density polyethylene (LDPE) and linear low density polyethylene (LLDPE).
20. A packaging material comprising the laminate according to any one of claims 1 to 19.